Intensive farming - Greenough, Elbert Ernest (My University, 1906)
Introduction: The subject of intensive farming is claiming the attention today of many thoughtful men. Especially is this true near large cities where the supply of vegetables and of dairy and poultry products is much in demand. By intensive farming we mean thorough and scientific cultivation of the land, so that the soil will produce crops to its limit of production. It is commonly followed by those engaged in the dairy business or truck farming. Most of the farmers engaged in crop farming have not yet learned the need of this intensive method of cultivation, nevertheless this country will eventually, sooner or later, practice intensive farming as the population increases. In foreign countries where the population is very dense such farming is the only kind followed. In France for instance families will subsist on the products of an acre or two of land. As our population increases it has been rapidly pushing westward making the desert blossom as the rose, but the western border has long since been reached and the word homestead has almost become obsolete. With the exception of a few small Indian reservations which still remain to be opened to the public, the good arable land has all been taken. These small reservations will be but a small item compared to the great army of men who are waiting to take advantage of such opportunities. That then is the solution of the problem. I believe that the small farm, well tilled, will give the solution, for two reasons, viz. the first cost both of land and equipment is small; and reliable labor for the farm is getting scarce and the small farm may be run with less hired help, thus saving wages and at the same time getting rid of much worry and vexation. To the young farmer the first point is of very great importance.
Citation: Greenough, Elbert Ernest. Intensive farming. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Agriculture; Intensive Farming; Small Farms; Crops; Theses